2020
DOI: 10.1371/journal.pone.0235569
|View full text |Cite
|
Sign up to set email alerts
|

The utility of DNA barcodes to confirm the identification of palm collections in botanical gardens

Abstract: The palm family (Arecaceae) is of high ecological and economic value, yet identification in the family remains a challenge for both taxonomists and horticulturalists. The family consists of approximately 2600 species across 181 genera and DNA barcoding may be a useful tool for species identification within the group. However, there have been few systematic evaluations of DNA barcodes for the palm family. In the present study, five DNA barcodes (rbcL, matK, trnH-psbA, ITS, ITS2) were evaluated for species ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Consistent with the diverse patterns found in most angiosperms [ 56 – 58 ], sequence divergence in non-coding regions is higher than that in coding regions. Variable chloroplast sequences have been widely used for plant phylogeny reconstruction [ 58 , 59 ] and for species identification [ 60 , 61 ]. However, among the chloroplast sequences which have most frequently been used in phylogeny reconstruction of tribe Maleae, such as trnH-psbA , trnL - trnF and trnG-trnS, etc .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the diverse patterns found in most angiosperms [ 56 – 58 ], sequence divergence in non-coding regions is higher than that in coding regions. Variable chloroplast sequences have been widely used for plant phylogeny reconstruction [ 58 , 59 ] and for species identification [ 60 , 61 ]. However, among the chloroplast sequences which have most frequently been used in phylogeny reconstruction of tribe Maleae, such as trnH-psbA , trnL - trnF and trnG-trnS, etc .…”
Section: Discussionmentioning
confidence: 99%
“…Plant material for most endangered, rare and narrowly distributed species are difficult to gather in the field, whereas botanical gardens and arboretums typically hold a wide diversity of well-documented living plant collections, which are important resources for the purpose of scientific research, conservation, display and education [13]. However, the morphological characters of plants growing in ex situ conditions may change, which may lead to misidentification if the plants lack complete or clear origin information.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mislabeling and misidentification before and after introduction into botanical gardens may also be a major cause of species misidentification. Misidentification of species collected from botanical gardens were reported in recent studies [11,13,14], which caused the incorrect inference of phylogenetic relationships and biogeographic history inferences. For instance, Le et al [13] found that 110 out of 669 palm samples (16.4%) collected from botanical gardens were misidentified, which can also be a problem for reintroduction efforts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations